An Error Analysis In Writing Descriptive Text Made By The Tenth Grade Students Of SMK Muhammadiyah 1 Surakarta In 2016/2017 Academic Year - Yuliana, Ana; , Nur Hidayat, M.Pd (2016)
This research is about an error analysis in writing descriptive text made by the tenth grade students of SMK Muhammadiyah 1 Surakarta in 2016/2017 academic year. The aims of this research are: (1) to know the types of error in the writing descriptive text made by the tenth grade students of SMK Muhammadiyah 1 Surakarta in their descriptive text. (2) to know the most frequent error made by the tenth grade students of SMK Muhammadiyah 1 Surakarta in their writing descriptive text. The researcher uses quantitative research, because the researcher only counts the percentage of errors from the data. To get the data, the researcher used elicitation method in her research. The subject of this research is the tenth grade students of SMK Muhammadiyah 1 Surakarta. The object of this research is the erroneous taken from 24 student's worksheet in writing descriptive text. The types of errors that found by researcher are lexical error, grammatical error, and discourse error. (1) the lexical error level is 75 errors or 38,5%, (2) the grammatical error is 118 errors or 60,5%, (3) the discourse error is 2 errors or 1%. The highest error is distortion with the total 38 errors or 19,5%.